Evaluation of Diabetic Wound Healing Activity of Novel Quercetin Topical Preparations - Nastiti, Christofori Maria Ratna Rini; Michelina, Ellisia; Wijayanti, Fabiola Rani; Gani, Michael Raharja (Sanata Dharma University, 2024)
Diabetic wound needs effective pharmacotherapy in order to accelerate the wound healing process and to prevent further infection. Quercetin (QUE) is one of flavonols which ispotential as an active ingredient for diabetic wound therapy, due to its anti-inflammatory and antioxidant activities. This current study evidenced wound healing activity of QUE topical preparations on the open wound of diabetic-induced subjects preclinically. The investigation focused on topical administration of QUE nanoemulgels and QUE micellar gels (0.2% w/w of QUE) on groups of diabetic-induced male Wistar rats. The quality of preparations in terms of organoleptic performance, pH, viscosity and spread-ability was physically characterized prior to topical administration to the wound. Punch biopsy (5mm) was applied to create the open wound. The visual observation of wound contraction area (in mm2) was carried out every three days. On the day 12th, after sacrificing the subjects, the wounded tissues were removed, fixed in 10% formalin and prepared for histology examination-hematoxylin and eosin staining. The results showed that the QUE nanoemulgels and QUE micellar gels were relatively comparable onthe physical quality as well as the wound healing activity. Their wound healing activities were remarkably faster compared to the untreated control group and it was showed fromthe histology study that the QUE nanoemulgels and QUE micellar gels successfully accelerate the wound healing process to the proliferation step if it was compared the untreated. In conclusion, QUE nanoemulgels and QUE micellar gels were potential to develop to accelerate the diabetic wound healing process.